Early sensory responses to plant-based diets in rainbow trout (Oncorhynchus mykiss) alevins: Impact on feeding behavior - Maud Martinat; Marie Lasserre; Elodie Baranek; Anne Surget; Anthony Lanuque; Frédéric Terrier; Cécile Heraud; Jérôme Roy (Aquaculture Reports)
Smell and taste are key sensory modalities involved in nutrient detection and feeding behavior in fish. In rainbow trout (Oncorhynchus mykiss), early growth can be compromised when fishmeal and fish oil are replaced by plant-based ingredients. However, the sensory mechanisms involved in feed detection at the alevin stage remain poorly understood. This study aimed to investigate how plant-based diets affect gustatory and olfactory responses during early development, and how these changes relate to feeding behavior. A postprandial kinetic experiment was conducted from first feeding to 30 days, using two diets: a commercial-like diet (C), composed of fishmeal, fish oil, and plant ingredients, and a fully plant-based diet (V). Fish were either fasted or sampled at 20 min, 2 h, 6 h, 10 h, and 24 h post-feeding. We measured the expression of genes involved in nutrient sensing (fatty acids, amino acids, sugars), taste modalities (sweet, salty, sour, acidic, bitter, umami), and calcium signaling in the olfactory rosette and tongue. We also analyzed neurotransmitter pathways (serotonin and dopamine), appetite-regulating neuropeptides in the brain, and intestinal hormones (CCK, ghrelin). Results showed that fish fed the V diet had significantly reduced growth performance (p < 0.01) and feed intake after 30 days (p < 0.01), associated with altered sensory gene expression. In C-fed fish, nutrient and taste receptors were mainly upregulated in the tongue, while in V-fed fish, expression shifted toward the olfactory rosette. C-fed fish also showed distinct calcium signaling patterns in the tongue and higher serotonin turnover. Expression of melanocortin 4 receptors (mc4ra, mc4rb) was elevated in V-fed fish (p < 0.05), suggesting central anorexigenic signaling. Together, these results indicate that V diets disrupt early feeding responses through changes in sensory perception and neuroendocrine regulation. This highlights the importance of considering sensory cues when formulating sustainable feeds for aquaculture.